Словозміна іменників у говірці села Березна на Холмщині (форми множини) - Осташ, Надія; Ostash, Nadiya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті висвітлено морфологічні особливості (іменникові форми множини) говірки села Березна на Холмщині. Аналіз виявляє як спільні риси з іншими говірками південно-західного наріччя, так і відмінності. Чимало морфологічних явищ пов’язано з особливостями фонетичної системи холмських говірок. У говірці збереглося багато архаїчних мовних явищ. The article discusses morphological peculiarities (singular noun forms) in the speech of the residents of the village of Berezno, Kholm province. Morphological system Kholm lokal dialects is extremely interesting and requires a thorough study in view of the fact that it is not specifically examined. The analysis reveals both common features and differences with other lokal dialects of south-western vernacular of the Ukrainian language. A significant number of morphological phenomena are related to phonological system of the Kholm lokal dialects (-е instead of ending -и in anaccented position, implementation of the ancient гы, кы, хы as гі,кі,хі in an unaccented position and as гє, кє, хє in anaccented positionetc.). The Kholm lokal dialects have maintained many archaic linguistic features: the remains of the dual nouns, active functioning uncontracted full forms of adjectives, verbal infinitive form on -чи, the remains of ancient forms of perfect and others.
Inflection of Nouns in the Lokal Dialect of the Village of Berezno, Kholm Province (Plural noun Forms)
Keywords: Березно; Холмщина; говірка; наріччя; іменник; морфологія; Berezno; Kholm province; lokal dialect; noun; morphology